Remarkable Electrical Conductivity Increase and Pure Metallic Properties from Semiconducting Colloidal Nanocrystals by Cation Exchange for Solution-Processable Optoelectronic Applications - Yoon, Sang Eun; Kim, Yongjin; Kim, Hyeongjun; Kwon, Hyo Geun; Kim, Unjeong; Lee, Sang Yeon; Park, Ju Hyun; Seo, Hyungtak; Kwak, Sang Kyu; Kim, Sang Wook; Kim, Jong H. (Small, 2023)
The authors report a strategic approach to achieve metallic properties from semiconducting Cu-Fe-S colloidal nanocrystal (NC) solids through cation exchange method. An unprecedentedly high electrical conductivity is realized by the efficient generation of charge carriers onto a semiconducting Cu-S NC template via minimal Fe exchange. An electrical conductivity exceeding 10 500 S cm−1 (13 400 S cm−1 at 2 K) and a sheet resistance of 17 Ω/sq at room temperature, which are among the highest values for solution-processable semiconducting NCs, are achieved successfully from bornite-phase Cu-Fe-S NC films possessing 10% Fe atom. The temperature dependence of the corresponding films exhibits pure metallic characteristics. Highly conducting NCs are demonstrated for a thermoelectric layer exhibiting a high power factor over 1.2 mW m−1K−2 at room temperature, electrical wires for switching on light emitting diods (LEDs), and source–drain electrodes for p- and n-type organic field-effect transistors. Ambient stability, eco-friendly composition, and solution-processability further validate their sustainable and practical applicability. The present study provides a simple but very effective method for significantly increasing charge carrier concentrations in semiconducting colloidal NCs to achieve metallic properties, which is applicable to various optoelectronic devices.
Keywords: Cation exchanges; Colloidal nanocrystals; Electrical conductivity; Exchange methods; Metallic properties; Optoelectronic applications; Semiconductor-to-metal transitions; Solution processable; Strategic approaches; Thermoelectric devices; cation exchange; colloidal nanocrystals; electrical conductivity; semiconductor-to-metal transition; thermoelectric devices